Youth Violence in Latin America
XVI, 234 p.
Keywords: This volume provides a systematic overview of the contemporary Latin American youth violence phenomenon. The authors focus specifically on youth gangs, juvenile justice issues, and applied research concerns, providing a rounded and balanced exploration of this increasingly important topic.